The Development of Hybrid-Learning Model Using Etno-Stem Approach for Education Students in Universitas PGRI Semarang - Fine Reffiane; Sudarmin Sudarmin; Wiyanto Wiyanto; S Saptono (International Conference on Science, Education, and Technology, 2021)
In this 21st century, learning process has two choices; online and offline learning. The old learning way (offline) suddenly has to be stopped due to the Covid-19 pandemic and be changed into online as the solution which expectedly bring positive effectiveness on skills of students in this century. According to (1) online learning should be able to make the knowledge and skill balanced. Hybrid learning model using Etno-STEM offers learning model in an interesting thematic way. The thematic way formed through Etno-STEM approach will be combined with Learning Management System (LMS) to make a dynamic learning. The use of LMS which demands ability of using digital and the unity of local wisdom expectedly helps students balance their knowledge and skills. This is in line with (2) that learning should balance the skill of natural behaviour and knowledge accompanied by local wisdom. The aim of this study is developing ability of 21st century of education students. It is going to investigate the advantages and disadvantages of Hybrid learning Model using Etno-STEM approach. True experimental design was applied. The result revealed that the readiness of supporting system was 86,17 % for server while 61.5 % for networking system and grouped into sufficient. Students’ interest for offline learning in Universitas PGRI Semarang was high (80, 50%) and grouped into interesting. In conclusion, this study result is matched with the learning system at present.